Increase in Antipsychotic Polypharmacy Treatment in Patients with Schizophrenia Between 1994-2000 and 2010 - Ceylan, Deniz; Aktener, Ahmet; B. Akdede, Berna; Alptekin, Koksal (Current Psychopharmacology, 2014)
Objective: The objective of this study is to determine the increase in the prevalence of antipsychotic polypharmacy in Dokuz Eylul University Psychotic Disorder Outpatient Unit over a period of 10 years. Methods: All accessible records of the patients, examined in the Dokuz Eylul University Psychotic Disorder Outpatient Unit between 1994 and 2000, and in 2010 were evaluated. Ninety one schizophrenia patients who had been examined between 1994 and 2000 and 102 schizophrenia patients who had been examined in 2010 were compared in terms of drug prescription patterns. Results: The point prevalence of antipsychotic polypharmacy showed a significant difference between two groups (p=0.022), polypharmacy increased from 32% to 49%. The number of first-generation antipsychotic (FGA) medications decreased from 46% to 26%, while the number of second-generation antipsychotic (SGA) medications increased from 71% to 99%. Conclusion: The prevalence of antipsychotic combinations both with other antipsychotics and other psychotropic medicines increased significantly over a period of 10 years.
Keywords: Antipsychotics